Assay of Diphtheria Vaccine Potency by Intradermal Challenge Test - E. I. Komarovskaya; О. V. Perelygyna (Эпидемиология и вакцинопрофилактика)
Relevance. Modern identifying potency (immunogenicity) of diphtheria toxoid tests are based on determining immunized animals resistance for administration challenge toxin or evaluation of protective antibodies level in serum. In Russia to assess the potency of diphtheria toxoid (DT) the challenge lethal method has been used for more than 60 years, challenge is based on determination of potency via its possibility to defend immunized animals from lethal doses of diphtheria toxin. This method is used as «golden standard». Last decade European Union Regulatory politic is headed to reduce of using animals in pharmaceutical practice, "The Three Rs" approach. In frameworks of this approach alternative methods of evaluating immunogenicity DT were purposed, particularly, intradermal challenge method. Within this test the potency of diphtheria toxoid is evaluated by its possibility to protect immunized animals from intradermal administration of diphtheria toxin. In the production of a number of foreign vaccines intradermal challenge test is used for assessing potency.Aim. Comparative characteristics of methods of lethal challenge test and intradermal challenge tests to determine the potency of diphtheria toxoid in combined vaccines and toxoids made in Russia.Materials and methods. Materials of domestic and foreign manufacturers were used in the work: combined vaccines for diphtheria prevention, diphtheria toxins, reference-vaccine. The determination of the potency of diphtheria toxoid was carried out on guinea pigs by pharmacopoeias methods: lethal challenge test and intradermal challenge tests.Results. To assess the potency of diphtheria toxoid using, a technique was used in accordance with WHO recommendations; for this, guinea pigs similar in sensitivity to diphtheria toxin to Dunkin Hartley pigs were selected. The suitability of the diphtheria toxin used in Russia for determining the potency of diphtheria toxoid by the method of intradermal challenge test was assessed when evaluating the effectiveness of vaccines for the prevention of diphtheria. Comparative tests of the intradermal challenge tests and lethal challenge tests were carried out to determine the potency of diphtheria toxoid.Conclusions. The conducted studies have demonstrated the fundamental possibility of using the intradermal challenge tests to assess the potency of diphtheria toxoid. However, for a number of factors, such as the variability of results, the number of animals, etc., the intradermal challenge tests is inferior to the method of lethal challenge tests in assessing the potency of diphtheria vaccines in routine practice.